Socialization of the Use of Semantic Scholar in Improving the Quality of Student Research: Pengabdian - Firman Sinaga; Liestyowati; Komang Trigita Juliastri; I Gusti Made Riko Hendrajana; Komang Shanty Muni Parwati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The following are the steps he took with one hundred and fifty students at the Institute of Tourism and International Business and Telkom Unversity. The result in this article show that The socialization in this article aims to teach students how to use the Semantic Scholar application to improve the quality of their article. One indicator of quality article can be seen from quality references. Semantic Scholar is an AI that offers a myriad of quality references to improve article quality. Some of the advantages of Semantic Scholar include the following: 1. Article Efficiency: With its unique ability to identify context and relationships, Semantic Scholar can save article time. Auhtors no longer need to sort through hundreds of articles just to find relevant ones. 2. Faster Innovation: With easier access to relevant article, innovation can happen more quickly. This can have a positive impact on various industries and disciplines. 3. Article Empowerment: Semantic Scholar empowers auhtors to explore various disciplines and gain a better understanding of their fields. 4. Open Access: One important aspect of Semantic Scholar is open access. This means that most of the content you find in it is freely accessible. This is a major step in democratizing access to knowledge. Based on this, auhtors believe that this socialization can gradually improve the quality of student article.